2017
DOI: 10.1021/acs.macromol.7b01590
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Poly(2-vinylpyridine)-block-Poly(4-vinylpyridine) Copolymers Containing Gold Nanoparticles

Abstract: We studied the phase behavior of the poly(2-vinylpyridine)-blockpoly(4-vinylpyridine) copolymer (P24VP) containing gold nanoparticles, by rheometry, small-angle X-ray scattering, transmission electron microscopy (TEM), and differential scanning calorimetry (DSC). Although both blocks of P24VP exhibited attractive interaction to gold precursors, unusual phase behavior was observed depending on the amount of gold nanoparticles. As the amount of gold nanoparticles increased, the order-to-disorder transition tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…In a pertinent example, Kim and coworkers showed that microphase-separated domains of P2VPb-P4VP preferentially absorb gold nanoparticles into the P4VP matrix at lower concentrations and then eventually populated both domains, albeit to a much lesser extent in P2VP domains, at increasing nanoparticle concentration (Figure 3). 84 The same concept extends to large organic guests as well. Hadjichristidis, Ruokolainen, and co-workers showed through infrared (IR) spectroscopy that bulky cholesteryl hemisuccinate (CholHS) can only partially hydrogen bond to P2VP segments (∼30%) regardless of excess CholHS loading.…”
Section: ■ Synthesis and Advancementsmentioning
confidence: 95%
“…In a pertinent example, Kim and coworkers showed that microphase-separated domains of P2VPb-P4VP preferentially absorb gold nanoparticles into the P4VP matrix at lower concentrations and then eventually populated both domains, albeit to a much lesser extent in P2VP domains, at increasing nanoparticle concentration (Figure 3). 84 The same concept extends to large organic guests as well. Hadjichristidis, Ruokolainen, and co-workers showed through infrared (IR) spectroscopy that bulky cholesteryl hemisuccinate (CholHS) can only partially hydrogen bond to P2VP segments (∼30%) regardless of excess CholHS loading.…”
Section: ■ Synthesis and Advancementsmentioning
confidence: 95%
“…Generally, solvents employed for self-assembly should be poor solvents for the core-forming block and effective or good solvents for the corona-forming block. Typically, one studies the self-assembly in non-polar solvents of BCPs with a non-polar corona-forming chains such as polydimethylsiloxane (PDMS), 25,26 polystyrene (PS) [2][3][4][5]27 or polyisoprene, 9,26,[28][29][30] and in polar solvents for BCPs with a polar corona-forming chain such as poly(acrylic acid), [31][32][33] or PEO, 17,[34][35][36][37][38] or polyvinylpyridine (P2VP), [39][40][41][42][43][44][45] or poly(N-isopropyl acrylamide). [46][47][48][49] Some authors have looked at two-component solvent mixtures, for example tetrahydrofuran/isopropanol (THF/iPrOH) to enhance the solubility of the core-forming block to promote self-assembly, 50 or hexane-iPrOH mixture to create a solvent in which micelles with both PDMS and P2VP corona chains are colloidally stable.…”
Section: Introductionmentioning
confidence: 99%
“…These morphologies include body centered cubic packed spheres, hexagonally packed cylinders (HEX), continuous gyroids, and alternating lamellae . Accordingly, the self‐assembly of the block copolymers can be a powerful tool to create functional materials and CPNs with tailored structures and, thereby fine‐tuning properties …”
Section: Introductionmentioning
confidence: 99%